Primary Health Care Strengthening and Universal Health Coverage in South Asia and Beyond: Status and Challenges - Rama Baru (Social Change, 2026)
During the last three decades, health systems globally have faced rising inequities in access to health services and a rise in the cost of care. The neoliberal health sector reforms of the 1980s and 1990s commercialised public systems and enlarged spaces for the market. Low- and low–middle-income countries were most affected by the health reforms, and the COVID-19 pandemic further weakened health systems in the Global South. Recognising the rising inequities and weak primary health care, there is an effort to correct the inequities.